Surgical Complications of Prepectoral Breast Reconstruction with Implants (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Reconstructive plastic surgeries with one-stage prepectoral implant placement in patients with breast cancer (BC) are becoming increasingly important. Good aesthetic results and high quality of life are the main incentives for performing such surgeries. The experience of using this intervention for more than 10 years in patients with BC, including after systemic combined treatment, allows us to evaluate its outcomes and the possibility of complications. This article presents the results of observation in the department of oncology and reconstructive plastic surgery of the mammary gland of patients after one-stage breast reconstruction with prepectoral placement of textured (45%) and polyurethane (47.5%) endoprostheses, as well as tissue expanders (7.5%). The observation period was 65 months. The study assessed the frequency of complications such as seroma, hematoma, "red breast" syndrome, ripling, diastasis of the wound edges, implant loss, capsular contracture of grades III-IV. In addition, clinical examples of some complications are given. Analysis of the literature and our own experience indicate that careful selection of patients and improvement of surgical technique contribute to the further dissemination of this method and minimization of the risk of possible complications.